Storytelling: a vocabulary booster for sixth graders - Andini, Febriya; Winarta, Ida Bagus Gde Nova; Candra, Komang Dian Puspita (Journal of Language and Applied Linguistics, 2020)
The Objective of this study was to determine the application of teaching English vocabulary using the storytelling method. The writer organizes English vocabulary in elementary school using the storytelling approach as a method of presenting content. The research used qualitative and quantitative methods. As research instruments, pre-test and post-test were used. The test was attended by 23 Students consisting of 13 female Students and 10 male Students. The results can be summarized as follows: in the pre-test, Students' mean was 4.3 and post-test was 8.7. The mean final post-test scores was 9.3. The results showed that the Students' vocabulary mastery was increased by using the storytelling method. This is because Students are interested and they enjoy the stories given. The use of storytelling could be seen as an alternative way of teaching vocabulary. The writer hope that these results can inspire language teachers to use storytelling in English classroom, especially when teaching vocabulary for elementary school.